Non‐Noble Metal‐Based Catalysts Applied to Hydrogen Evolution from Hydrolysis of Boron Hydrides. Issue 7 (14th April 2021) - Wang, Yan; Hu, Zhe; Chen, WeiHua; Wu, Shiwei; Li, Guode; Chou, Shulei
Abstract : Hydrogen energy is proposed as a promising energy replacement to resolve the current energy problems for sustaining the long‐term development of human society and eventually achieving the hydrogen economy. The evolution of hydrogen from the hydrolysis of boron hydrides is considered as one of the most secure and effective strategies. Seeking appropriate non‐noble metal‐based catalysts is the vital step that is needed to improve the sluggish kinetics of the hydrolysis process. Herein, the evaluation approaches related to the catalytic activities, kinetics, and stability are first summarized. Then, different non‐noble metal‐based catalysts based on single metals and their alloys, metal phosphides, borides, and oxides, and even single‐atom catalysts, are systematically discussed. The relationships among the synthesis methods, material structure, compositions, and catalytic activities are also critically reviewed. Finally, the challenges and perspectives for future non‐noble metal‐based catalysts for hydrolysis of boron hydrides are included to aid in the development of sustainable and clean hydrogen energy. More importantly, the current research is mainly focused on the fundamental research, whereas the report on the practical application for the catalyzed hydrolysis of boron hydrides is less. Developing portable hydrogen generators as hydrogen sources for portable electric power is a potential strategy. Abstract : The authors summarize the recent development of non‐noble metal‐based catalysts for the hydrolysis of boron hydrides, including single metals and their alloys, metal phosphides, borides, and oxides, and even single‐atom catalysts. By heteroatom doping, constructing multifarious morphologies, optimizing preparation strategies, and coupling with other materials, the catalytic activities of non‐noble metal‐based catalysts are significantly improved.